Respuesta :
Answer:
f(3) = 22
Step-by-step explanation:
To find f(3), we need to first find f(2) since we have been given f(1) to be equal to 2.
f(n)=3f(n-1)+1
To find f(2), simply replace all the n in the function by 2
f(2) = 3f(2-1) + 1
=3f(1) + 1
but we were given f(1) to be equal to 2 from the question, so we will simply substitute f(1)=1 in the function
f(2) = 3f(1) + 1
=3(2) + 1
= 6 + 1
=7
so our f(2) = 7
We can now proceed to find f(3), to find f(3) simply replace all n by 3
f(3) = 3f(3-1) + 1
=3f(2) + 1
But we have gotten f(2) to be 7, so we simply substitute f(2) = 7 in the function.
f(3) = 3f(2) + 1
=3(7) + 1
=21 + 1
= 22
f(3) = 22
Therefore f(3) is 22